Family Photographs of the Tuvans Across Decades - Lamazhaa, Chimiza K.; Mainy, Shenne B. (The New Research of Tuva, 2025)
The article analyzes family photographs of Tuvans taken over various periods, from the 1920s to the 2020s. The authors regard family photographs as a unique historical and cultural source reflecting sociocultural dynamics, the transformation of family traditions, norms, and representations in Tuva. The study draws on archival and private photo collections, photographs published in Tuva’s mass media, and records of family histories collected during field expeditions from 2022 to 2024.The analysis is grounded in R. Barthes’ theory of denotative and connotative meanings of photographs. The methodology incorporates visual analysis, a comparative-historical approach, and elements of family history and microhistory. This enables the researchers to trace changes in photographic imagery, narratives, and aesthetics associated with successive waves of modernization, urbanization, and the transition to digital technology.Family photography in Tuva reflects key phases of ethnocultural modernization: in the prewar decades, photographs predominantly recorded ritual moments, kinship ties, and traditional ways of life; since the mid-20th century, new subjects have emerged, with an emphasis on nuclear families, new forms of festive culture, and pronounced conformity to Soviet norms. From the late 1990s and into the 21st century, digital images dominate, the genre range expands, and an explicit aspiration emerges toward visualizing ethnocultural symbols, showcasing ethnic identity, and displaying large multigenerational families.The study identifies the role of Tuvan family photographs in shaping collective memory and identity and examines the development of the genre as a phenomenon linked to shifts in social practices, family structure, and conceptions of everyday and festive appearances of the Tuvans.
Keywords: Tuvans; history of Tuva; family photography; 20th century; Soviet history; representation; photographing; ethnicity; national costume; everyday life; family